Bilateral agreements for the protection of migratory birdlife: the implementation of the China-Australia Migratory Bird Agreement (CAMBA). Issue 1 (May 2019) - Hamman, Evan
Abstract : Every year, millions of migratory birds journey along the East Asian-Australasian Flyway (EAAF). The scope of the EAAF encompasses Asia Pacific nations like Australia, New Zealand, China, Japan, South Korea, Vietnam, Malaysia and Indonesia. The effective conservation of these birds rests upon the implementation of bilateral legal agreements as well as non-binding regional initiatives along this North-South nexus. This article evaluates the implementation of one of the most important bilateral bird agreements in the region – the China-Australia Migratory Bird Agreement (CAMBA). The main obligations in CAMBA are identified; as are the legal initiatives adopted by both China and Australia which reflect CAMBA's obligations. Whilst Australian law makes specific reference to CAMBA, Chinese law is far less direct, though perhaps no less effective. The argument is made that the findings in this article have relevance for an improved understanding of the mechanisms for transboundary governance of migratory birdlife, especially in the Asia Pacific.